2021
DOI: 10.48550/arxiv.2109.00902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 confines recreational gatherings in Seoul to familiar, less crowded, and neighboring urban areas

Abstract: Understanding human urban dynamics is essential but challenging as cities are complex systems where people and space interact. Using a customer-level data set from a leading Korean accommodation platform, we identify that urban hierarchy, geographical distance, and attachment to a location are crucial factors of social gathering behaviors in urban areas. We also introduce a model that incorporates the factors and reconstructs the key characteristics of the data. Our model and analysis show that COVID-19 leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Various non-pharmaceutical interventions imposed by governments and agencies have enforced people to substantially change their lifestyles and reduce daily activity patterns, reducing trips to urban amenities such as restaurants, bars, and entertainment establishments 19 . While such behavior changes have had significant impacts on our physical health and activities 20,21 and mental wellbeing 22 , studies have also suggested their impact on social encounters in urban environments, affecting the social fabric of cities we live in 23 . The aftermath of the pandemic has brought also significant changes in behavior in our cities, including less use of public transportation 24 , more hours working from home 25 , and higher usage of online food and goods delivery services 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Various non-pharmaceutical interventions imposed by governments and agencies have enforced people to substantially change their lifestyles and reduce daily activity patterns, reducing trips to urban amenities such as restaurants, bars, and entertainment establishments 19 . While such behavior changes have had significant impacts on our physical health and activities 20,21 and mental wellbeing 22 , studies have also suggested their impact on social encounters in urban environments, affecting the social fabric of cities we live in 23 . The aftermath of the pandemic has brought also significant changes in behavior in our cities, including less use of public transportation 24 , more hours working from home 25 , and higher usage of online food and goods delivery services 26 .…”
Section: Introductionmentioning
confidence: 99%